Global research trends on innate lymphoid cells in the brain, gut and lung field: a bibliometric and visualized analysis - Huang, Jianliang; Deng, Kun; Liu, Ying; Xia, Mingkai; Lei, Mingsheng; Wu, Minghua (Frontiers in Immunology, 2024)
Background: ILCs play important roles in the brain, gut, and lungs. Researchers are attempting to establish a research framework on the brain-gut-lung axis using ILCs. However, no one has yet conducted a bibliometric analysis to summarize the findings. In this study, we utilized bibliometrics to analyze the emerging trends and focal areas of ILCs in the brain, intestine, and lung. We aim to provide references for future research on the brain-gut-lung axis. Methods: To conduct a comprehensive bibliometric analysis on ILCs in the fields of brain, intestine, and lung, we utilized software such as HistCite, VOSviewer, and CiteSpace. Our analysis focused on various aspects, including the number of publications, countries, authors, journals, co-cited documents, and keywords. This approach allowed us to gain valuable insights into the research landscape surrounding ILCs in these specific fields. Results: A total of 8411 articles or reviews on ILCs in the fields of brain, intestine, and lung were included. The number of published articles has shown a consistent upward trend since 2003. A total of 45279 authors from 99 countries have contributed to these articles. The United States has the highest number of publications (n=3044) and the most cited articles (TGCS=210776). The top three published authors in this field are David Artis, Marco Colonna and Andrew NJ McKenzie. The journal Immunity is the most authoritative choice for researchers. The main research focuses in this field include NK cell, ILC2, tumor immunity, multiple sclerosis, inflammatory bowel disease, airway inflammation, RORγT, and immunotherapy. In recent years, cancer and tumor microenvironment have emerged as hot keywords, particularly immunotherapy, PD-1 related directions, indicating a potential shift in research focus. Conclusion: European and American countries have been pivotal in conducting research on ILCs, while China has produced a significant number of publications, its impact is still limited. Tumors are likely to emerge as the next focal points in this field. The connection and regulation between the brain and the lung are not yet fully understood, and further investigation is necessary to explore the role of ILCs in the brain-lung axis.